Oral Hygiene Practices Followed by Physically and Mentally Challenged People - LAKSHME, P.S. THANA; SASANKA, KEERTHI; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
Physically and mentally challenged individuals are a unique set of patient population whose health demands and oral care demands are considerably different from the normal patient population. Therefore, this study aimed to assess the oral hygiene practices followed by physically and mentally challenged people in Madurai district. The study was carried out in a homogeneous population of 100 physically and mentally challenged participants. The self structured questionnaire was distributed among the targeted population. The data were collected and presented in the form of pie charts.The population mostly consisted of mentally challenged people who were even unaware of the basic hygiene to be maintained whereas the rest of the population were visually and hearing impaired persons and handicaps. The most surprising result of the study is that the population was aware of their impact of disability on oral health.The result establishes that there exists a better awareness and knowledge among caretakers on oral hygiene practices that should be followed on such differently abled persons.Creating awareness and providing knowledge on oral hygiene practices would provide better oral health and thus avoiding complications in systemic health.